Peningkatan Minat dan Hasil Belajar IPA melalui Media Herbarium Berbantuan Big Book - Eddyani, Desty; Sudiyana, Benedictus; Kustanti, Binar (EDUKASI, 2024)
This research aims to address the lack of optimal use of learning media in science education (IPA) at SDN Pranan 01, where teachers rely solely on reading materials as the primary source of learning. This limitation hinders the students' learning experience and interest in the subject. To overcome this issue, a more creative and innovative approach is necessary, specifically through the use of a herbarium integrated with Big Book media. The objective of this study is to examine the effectiveness of using a herbarium combined with Big Book in improving students' interest and learning outcomes in science education. The research employed a Classroom Action Research (CAR) method, consisting of four stages: planning, implementing the action, observing and evaluating, and reflecting. The results demonstrated a significant improvement in both student interest and learning outcomes. In the first cycle, the average index of learning interest was 59.01%, with 73% of students achieving mastery in their learning outcomes. In the second cycle, the average learning interest index increased to 65.47%, with 93% of students reaching the desired level of mastery. The findings suggest that the use of herbarium and Big Book media effectively enhances student engagement and performance in science learning. It is concluded that integrating creative learning media, such as herbarium with Big Book, can positively impact students' interest and academic achievement.